Determinants of job satisfaction in the Lebanese construction sector. (23rd October 2019) - Vrontis, Demetris; Chaarani, Hani El; Nemar, Sam El; Yamak, Bacel
Job satisfaction is the fulfilment or enjoyment that a person derives from their job. Job satisfaction has been a focal point of social sciences studies since the early 1900s, due to its substantial impact on employees' mental health, as well as its influence on the workplace atmosphere and productivity. This study aims to ascertain the determinants of job satisfaction in the Lebanese construction sector. The primary data was gathered through a quantitative structured questionnaire, while the sample amounted to 106 employees in the construction sector. The results of the study revealed a significant positive relation between payment (salary), financial benefits, promotion, and personal job satisfaction. In addition, this study revealed a non-significant connection between gender, age, package incentives, job security, rank, relationships with co-workers, stress/workfamily conflict, designation (social recognition), and job satisfaction.